The effective internal audit function as part of a sound corporate governance structure : the case study of Saldanha Bay Municipality - Dichabe, Omphemetse Lorraine (Stellenbosch : Stellenbosch University, 2020)
Thesis (MMil)--Stellenbosch University, 2020.